Physical and Verbal Violence in Family Interpersonal Communication - Lie, Vincent Septian; Yuliana, Nina (SEAN Institute, 2024)
This research examines the phenomenon of physical and verbal violence in family interpersonal communication. The general objective of this study is to identify the contributing factors to physical and verbal violence within the family context, explore the impacts on victims, and formulate preventive solutions to mitigate such violence. The theoretical framework employed in this research is the social exchange theory, utilized to comprehend how victims and perpetrators of violence within the family evaluate their actions. The theory further aids in understanding the decision-making processes to maintain family relationships and the dynamics of violence patterns and compensations within the family context. The research methodology applied is a case study using a qualitative-descriptive approach, involving one key informant as the dominant victim, one supporting informant as the perpetrator, and two additional informants as witnesses. The research findings indicate that physical and verbal violence in family interpersonal communication emerges due to various factors, including communication barriers and indications of internal conflicts within individuals. The perceived impacts on victims significantly influence their lives, ultimately affecting their responses to these issues.